Mechanical properties of interfacial phases between Sn-3.5 Ag solder and Ni-18 at. % W barrier film by nanoindentation. Issue 2 (7th April 2015) - Chew, C.S.; Durairaj, R.; Haseeb, A. S. M. A.; Beake, B.
Abstract : Purpose: – The purpose of this paper is to investigate the hardness and elastic modulus on interfacial phases formed between Sn-3.5Ag solder and Ni-18 at. % W alloy film by nanoindentation. It has been found that a ternary amorphous Sn-Ni-W layer formed below Ni3Sn4 IMC at the interface. In this study, mechanical properties of the IMC formed between SA solder and Ni-18 at. % W film after six times reflows were performed by nanoindentation. Design/methodology/approach: – The characterization was carried at 25°C, and 100 indents were generated. The elastic modulus and hardness were investigated. Findings: – The results showed that hardness of Ni3Sn4 IMC was higher than amorphous Sn-Ni-W phase. A slight bigger indent was observed on the Sn-Ni-W layer compared with that on the Ni3Sn4 IMC. Lower topographical height in the Sn-Ni-W layer indicated that the Sn-Ni-W phase was softer compared with the Ni3Sn4 IMC. The lower hardness and soft Sn-Ni-W phase is significantly related to the amorphous structure that formed through solid-state amorphization. Originality/value: – There are no publications about the indentation on the interfacial between the Ni-W layer and the Sn-Ag solder.